2021
DOI: 10.3389/fpsyg.2021.628223
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference in Pain Management Among Adult Cancer Patients in Saudi Arabia: A Cross-Sectional Assessment

Abstract: ObjectiveTo compare gender differences in pain management among adult cancer patients in Saudi Arabia and to explore the predictors associated with attitudinal barriers of cancer patients to pain management.MethodsA descriptive cross-sectional study was conducted among 325 cancer patients from tertiary hospitals in Saudi Arabia.ResultOf the total participants, 67.4% were women (N = 219) and 32.6% were men (N = 106). The overall mean scores of the attitudinal barriers questionnaire were 49.51 ± 13.73 in men and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
3
4
0
Order By: Relevance
“…Males reported higher communication scores in most areas than females did. These results are in line with those from a study on communication in cancer patients with pain [23].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Males reported higher communication scores in most areas than females did. These results are in line with those from a study on communication in cancer patients with pain [23].…”
Section: Discussionsupporting
confidence: 92%
“…Higher communication scores were expected from older patients [18], male patients [19,20], and patients with higher levels of education [17,21]. Higher scores were also expected from patients at initial disease stages [22], those without comorbidity [23], those who had previously received oncological treatment or treatment from the same doctor or group of nurses, and those with higher levels of communication competence [10]. Higher scores were also expected in communication with nurses [24].…”
mentioning
confidence: 99%
“…The observed barriers to pain management in our study resonate with patterns identified in the broader Middle Eastern context, suggesting a regional trend shaped by cultural and educational factors that influence patient attitudes. Our findings align with barrier levels documented in Jordan [ 17 ], Saudi Arabia [ 18 ], and the United Arab Emirates [ 19 ], highlighting a regional consistency potentially rooted in shared cultural and health beliefs. Notably, the Barriers Questionnaire (BQ) scores from this study exceed those from diverse cultural settings such as the United States, Turkey, and Ireland, suggesting that culture influences the perception and management of pain across different societies [ 20 , 21 , 22 , 23 ].…”
Section: Discussionsupporting
confidence: 87%
“…Across a variety of disease states, male patients have been shown to receive better care than female patients. 1618 In our study, more rules were reviewed for male patients (male, 57.4%, female 42.6%), but the clinician intervened more often for female patients. It is unclear whether these male-to-female rule proportions follow the gender split of hospitalized patients during the study timeframe, which could be an influencing factor on number of rules per gender.…”
Section: Discussionmentioning
confidence: 88%